Analysis of Factors Affecting the Mental Health Crisis of Coronavirus Disease Infection in Java Island - Diah Priyantini; Nursalam Nursalam; Tintin Sukartini (Jurnal Ners, 2021)
Introduction: Corona virus disease 2019 (COVID-19) is a health problem that is still a health emergency in the world and causes mental health crisis. The purpose of this study was to analyze the factors that influence the mental health crisis of COVID-19 infection on the island of Java.Methods: A cross sectional study between June-July 2020 in Java Island, Indonesia with 1.218 respondents selected using convenience sampling. The independent variable were demographic, individual internal, psychological factors and the dependent was mental health crisis. Data was measured by demographic information, knowledge and attitude questionnaires, depression anxiety stress score, the brief 28-item COPE Inventory, questionnaire on problem faces and crisis mental health emergencies. Analysis data is conducted by chi square and multivariate logistic regression.Results: The relation of demographic, individual internal and psychological factors were significant to crisis mental health and P <0.05. After adjusted with logistic regression, psychological factors have more significant relation and the highest relation was found in stress level with P = 0.000 and CI 95% was 1.064 – 2.131.Conclusion: The contributing factor that has the strongest relationship with a mental health crisis is the level of stress that people experience. The biggest contribution that causes disruption of psychologic conditions and mental health is psychological factors, which include levels of anxiety, stress, coping mechanisms and problems faced.